Education in Linguistic Subjects at A School That Focuses on Language (Eurasian Scientific Herald, 2023)
The article is focused on the challenges faced when teaching theoretical subjects such as general linguistics, theoretical grammar, lexicology, translation theory, stylistics, and text interpretation in the context of emerging linguistic fields. The argument is presented and supported that the language theory university curriculum must be greatly revised and expanded due to the impact of various disciplines including communicative linguistics, pragmalinguistics, cognitive linguistics, and linguoculturology